What is youth participation? - Checkoway, Barry (Children and youth services review, 2011)
Youth participation strengthens personal and social development, provides expertise for children and youth programs and services, and promotes a more democratic society, but questions arise about its most fundamental phenomena. Lacking agreement on its basic content, however, youth participation as a field of practice and subject of study will be limited. This paper examines what we know about youth participation, general propositions which are substantiated by research or practice, and unanswered questions or unresolved issues which remain for future work. It draws upon various academic disciplines and professional fields, in order to contribute to knowledge development and advance the field. ► Youth participation contributes to social development, program decisions, and democratic society. ► We examine general propositions substantiated by research or practice, and unanswered questions remaining for future work. ► Literature is reviewed from various academic disciplines and professional fields.